Publish or the Population Perishes: The Challenges of Regional Publishing in Public Health. (July 2019) - Binns, Colin; Low, Wah Yun
The publication of information is essential for expanding the benefits of public health throughout the Asia-Pacific region. All academics are familiar with the adage "Publish or perish, " but for public health, this should be rewritten as "Publish or the population perishes." Publication and communication in public health continues to undergo rapid change. There are many challenges that a regional journal faces. The number of printed journals is beginning to decline. Digital publishing and extensive databases and search engines have become the only practical way to access data. But the advent of digital publishing has seen the arrival of profit-making entrepreneurs. Whether a Journal is in the printed form or digital, it remains the key communication in public health and ultimately improve the health of the people. The Asia-Pacific Journal of Public Health (APJPH), which is owned by Asia Pacific Academic Consortium for Public Health ( APACPH ) and published by Sage ensures that your data gets maximum digital exposure in the region where it can make a difference. Over the years, APJPH has increased its impact factor and gained in prestige. Although impact factor of a journal is important in documenting the recognition of work by academics, it does not necessarily reflect importance to our region. There needs to be a re-evaluation of publication and communication strategies so that all citizens of the Asia-Pacific region benefit.